PERSEPSI MAHASISWA TERHADAP TOLERANSI BERAGAMA DI MEDIA SOSIAL TIKTOK (STUDI FAKULTAS AGAMA ISLAM UNIVERSITAS MUHAMMADIYAH METRO) - siti puji; Kuliyatun; Cahaya Khaeroni; Guntoro (Universitas Muhammadiyah Metro, 2026)
Tolerance is defined as the ability to be open and accept differences that come from various ethnic groups, skin colors, languages, customs, cultures, languages, and religions. Based on the current digital era, social media has become a popular and significant platform in disseminating information and facilitating social interaction, one example is the tiktok application. This study aims to determine how Muhammadiyah Metro University students, especially students of the Faculty of Islamic Religion, understand, respond to, and participate in issues of religious tolerance on social media. Tiktok social media can increase religious tolerance through content, opinions, and discussions about religion. According to researchers, Tiktok social media is one of the ways that can influence the perception of students of the Faculty of Islamic Religion towards religious tolerance. This research uses quantitative methods. The population in this study were 85 students of the Faculty of Islamic Religion class of 2021 who came from three study programs, namely, PAI, KPI, and PIAUD. This study uses a cluster random sampling technique, namely random sampling according to the area or region of a particular population. The analysis used validity test, reliability test, normality test kolmogorov smirnov, homogeneity test, hypothesis test or t test. The results of hypothesis testing using the t test (partial test) and f test (simultaneous test) show that the hypothesis is accepted, with the sig value obtained. 0.000 which means less than 0.05. The test criterion is if the sig value. t test <0.05 rejects H0 and accepts Ha. This result means that H0 is rejected and Ha is accepted, thus it is concluded that the perception of students of the Faculty of Islamic Religion towards religious tolerance on Tiktok social media is good. And the results obtained regarding student perceptions of religious tolerance on Tiktok social media are included in the “Good Enough” category with a percentage of 43.0%. And the factors that influence students' perceptions of religious tolerance on Tiktok social media are divided into 2, namely the first internal factors consisting of user interaction with content, the influence of influencers or content creators who are followed, the quality and context of comments and discussions. Then the second external factor consists of the TikTok algorithm, visual and narrative representation in videos, exposure to content from various cultures and religions